A temporary glacier‐surge ice‐dammed lake, Braganzavågen, Svalbard. (17th January 2018) - Lyså, Astrid; Larsen, Eiliv A.; Høgaas, Fredrik; Jensen, Maria A.; Klug, Martin; Rubensdotter, Lena; Szczuciński, Witold
Abstract : A prominent thrust‐moraine system formed in the inner van Mijenfjorden, Svalbard, during a surge event in a tributary fjord, creating a large temporary lake. Based on geomorphological, sedimentological, stratigraphical and chronological data, the lake began to form shortly after 648–551 cal. a BP. At its maximum, the lake covered an estimated area of 77 km 2 with a water volume of 1.2 km 3 . Lake sediment up to 80 cm thick was rapidly deposited on top of terrestrial and marine sediments. At its maximum extent, the short‐lived lake was the largest of any known Holocene lake in Svalbard. Modern river discharge would fill the lake to its highest shoreline at 23 m a.s.l. in only one season. Drainage was stepwise, as evidenced by four shorelines and abandoned drainage channels. This study has taken advantage of a unique suite of data available for such an ice‐dammed lake. The results demonstrate the power of a multidisciplinary approach for recognizing lake events in the geological record, which is essential given the low preservation potential of such sediments.